Auch Leitlinien müssen hinterfragt werden dürfen = Even guidelines must be allowed to be questioned - Kulu, Yakup; Hackert, Thilo; Debus, Jürgen; Weber, Marc-André; Büchler, Markus W.; Ulrich, Alexis (Der Chirurg, 2016)
No Abstract available for this article.